Water management for industrial development, energy conservation, and subjective attitudes: a comprehensive risk-oriented model to explore the tolerance of unbalanced allocation problem. Issue 1 (23rd August 2021) - Yu, Yangping; Xie, Yulei; Ji, Ling; Zhang, Jinbo; Cai, Yanpeng; Yang, Zhifeng
Abstract: In this study, a new concept concerning comprehensive characteristics of water resources utilization as an index for risk modeling within the water allocation management model is proposed to explore the tolerance of unbalanced allocation problem under the water–energy nexus. The model is integrated with interval two-stage stochastic programming for reflecting system uncertainties. These uncertainties are associated with the industrial production feature and the decision-making process. With respect to the water–energy nexus, energy proposed is mainly focused on the consumption intensity of water purification and transportation from different water sources. The developed model is applied for industrial water resources allocation management in Henan province, China. Multiple scenarios related to disparate energy consumption control and the comprehensive risk levels are simulated to obtain a reasonable trade-off among system profit, comprehensive risk, and energy consumption. The results indicated that the strict comprehensive risk management or energy consumption control measures could cause damage to system benefit owing to decreasing the flexibility of industrial water resources distributions, and the preliminary energy consumption or the comprehensive risk control would be beneficial to moderate the conflict between industrial sectors and water resources, and accelerate industrial structure transformation in the future. HIGHLIGHTS: A comprehensive risk-oriented industrial water resources management model is proposed. Uncertainties are reflected as stochastic and interval information. Energy–water nexus is a constraint index for water purification and transportation. The tolerance of unbalanced allocation problem is explored. Trade-off among system profit, comprehensive risk, and energy consumption is analyzed. Graphical Abstract